El trabajo realizado por adolescentes y la violación al derecho a la educación - María de los Ángeles, Méndez Satián (2021)
SUMARY O ABSTRACT Constitution of the Republic of Ecuador promulgated in 2008 made significant progress in recognizing the adolescents' rights, including them within a group of priority attention and attributing a shared responsibility between the State, society, and the family to be protected, considering them as the future of our country. Due to the economic situation our country has is going through. Also, there is a large number of adolescent workers in precarious conditions. The Labor and the Childhood and Adolescence Codes have established that adolescents over 15 years of age are productive entities. They can sign employment contracts, care that the activities to be carried out do not obstruct their proper physical, psychological and educational training. The working adolescent will only be able to work 6 hours a day and five days a week without neglecting their academic activities. International and national regulations have recognized the right to education as a fundamental right of human beings, and it must be of quality and free. Adolescents who work should be encouraged by their parents and employers to continue with their academic life since only academic training will allow the adolescent to have better working conditions. This research allows establishing that even with the public policies implemented by the State. There is a violation of the right to education by the employers of adolescent workers, which forces them to carry out long hours, preventing them from attending educational centers or due to the entrusted activities and financial need to abandon their studies. Keywords: the right to education, fair remuneration. Reviewed by: Ms.C. Ana Maldonado León ENGLISH PROFESSOR C.C.0601975980